INVESTMENT MANAGEMENT STRATEGY IN FINANCIAL MARKETS - Vunjak, Nenad; Stojanović, Petra (ECONOMICS - INNOVATIVE AND ECONOMICS RESEARCH JOURNAL, 2022)
The subject matter of this research is investment management and its forms practiced in developed financial markets. The goal of this research is to elaborate on the strategies and characteristics of investment companies, hedge funds, venture capital funds, and LBO funds. Investments companies deal with professional management of financial assets of individual and institutional investors. Investment companies also deal with funds management. Hedge funds establish a pool of assets to invest in securities. The strategy of hedge funds is: aggressive growth, unpayable securities, financial markets, and market neutrality. Venture capital funds use the capital of investors to finance entrepreneurs and promising companies. They function as general partners, while the investors are limited partners. LBO funds use credits to finance acquisitions of companies. They collect their assets by: issuing shares, speculative bonds, and private placement of debt securities. Keywords: investment companies, hedge funds, venture capital funds, LBO funds, general and limited investment partners.